Orthodox Christianity and Economy. The Review of the Russian Research, Dissertations, and Conferences Disputes on Social-Economic Approaches а Russian Orthodox Church in XIX-XXI Centuries. - ЗабаевИван Владимирович (Journal of Economic Sociology, 2010)
Detailed description in the text